Hukuman Cambuk dan Pengaruhnya Terhadap Kesadaran Hukum Masyarakat - Asna A (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the implementation of caning punishment and its influence on the level of public legal awareness. The research employs a socio-legal approach with a descriptive-analytical method. Data were collected through a literature study of legislation, related qanun, as well as Islamic law and national law literature, supported by empirical data from social conditions in the community. Data analysis was conducted qualitatively to illustrate the relationship between the application of caning punishment and changes in legal behavior among the public. The results of the study indicate that caning punishment has an impact on public legal awareness, particularly in terms of compliance with the norms of Islamic Sharia law. This punishment creates a deterrent effect and functions as a means of legal education in a social context. However, its effectiveness is greatly influenced by the public’s understanding of the purpose of the punishment, the consistency of law enforcement, and the approach employed by law enforcement officers. If caning emphasizes only the repressive aspect without being balanced with legal guidance and education, the resulting legal awareness tends to be superficial and temporary. This study concludes that caning punishment can contribute to enhancing public legal awareness if it is applied proportionally, fairly, and in alignment with humanitarian values and local wisdom. Therefore, strengthening the educational aspect and legal socialization is necessary so that caning is understood not merely as a sanction but also as an instrument for moral and social development within society.